Rancang Bangun Sistem Irigasi Tetes dan Monitoring Kualitas Lahan Pertanian Tadah Hujan Berbasis Web - Ghilmi Fajar; Minarto Minarto; Uus Muhamad Husni Tamyiz (Journal of Information System Research (JOSH), 2023)
In this study the object studied was rainfed agricultural land, this type of agriculture depends on rainwater so good management is needed in managing the cropping system to produce optimal results. The drip irrigation system can be used when the dry season arrives to support the quality of moisture in the soil and soil quality monitoring is carried out to determine the planting of corn plant seeds. The prototype method is used in designing drip irrigation systems and monitoring the quality of agricultural land. System design using the prototype method is one of the software design techniques used in designing web applications. The application is designed using the PHP programming language and the framework used is CodeIgniter (CI), so the Unified Modeling Language (UML) is designed. Internet of Things uses NodeMCU ESP8266 as a microcontroller that will connect to the web. The results of the sensor test for 30 minutes on soil moisture can be maintained at 40-80% humidity when drip irrigation is running. When the water in the tank runs out and drip irrigation is not running, the soil moisture will decrease by 30%, the soil pH value is at a value of 6-7% and the temperature value is at 21-34 degrees Celsius, the soil quality is suitable for planting corn seeds. The drip irrigation system can be used when the dry season arrives to keep the soil moist and this land monitoring is useful for farmers in determining good land conditions for planting corn seeds. The system design can be further developed by adding sensors to the water control in the drip irrigation tube to measure the amount of water used.